Analyzing The Effect Of Increasing Growth And Motoric Development Of Infants Aged 6-11 Months Who Are At Risk Of Stunting With Baby Spa Treatment - Ikha Prastiwi; Rifka Alindawati (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Optimal growth and development of baby can be carried out by stimulation. Stimulation can be given through active tactile stimulation to baby, one of which is with massage, solus per aqua (SPA). This study was to analyze the improvement of growth and motoric development of infants aged 6-11 months who are at risk of stunting with Baby SPA Treatment. Research method with Quasi-experimental quantitative research, pre and posttest approach with two group intervention design with a total sample of 30 respondents. Statistical test using Paired Sample t-test. The results showed an average change in the baby SPA group before 8,413 grams and after treatment 8,930 grams, while in the baby massage group before 8,260 grams and after treatment 8,460 grams. The difference in average body weight in the baby SPA group was 517 grams, the baby massage group was 200 grams (p=<0.001). The average height of the baby SPA group before the treatment were 73.7cm and after the treatment 75cm, while in the baby massage group before the treatment 71.7cm and after the treatment 72.9cm. The difference in the average height of the baby SPA group was 1.36 cm, while the baby massage group was 1.2 cm (p = <0.001). Changes in the average motoric development of the baby SPA group before 9.07 and after treatment 9.93, while in the baby massage group before 9.00 and after treatment 9.87. The difference in the average motoric development the baby SPA group was 0.86, while the baby massage group was 0.87 (p=0.55). In conclusion, there are differences in the average value of weight and height gain before and after treatment, there is a difference in the mean difference in weight and height between baby SPA group and baby massage, there is no difference in the average difference in motoric development between baby SPA group and baby massage. Suggestions for baby SPA treatment as one of complementary care.